Mechanistic Insights into the Inhibitory Activities of Chemical Constituents from the Fruits of Terminalia boivinii on α‐Glucosidase. Issue 7 (4th July 2022) - Dlamini, Bongani Sicelo; Chen, Chiy‐Rong; Chen, Yu‐Kuo; Hsu, Jue‐Liang; Shih, Wen‐Ling; Chang, Chi‐I
Abstract: Regulation of key digestive enzymes is currently considered an effective remedy for diabetes mellitus. In this study, bioactive constituents were purified from Terminalia boivinii fruits and identified by 1 H‐NMR, 13 C‐NMR and EI‐MS. In vitro and in silico methods were used to evaluate α‐glucosidase, α‐amylase, and lipase inhibition activities. Compounds 1, 2, and 4–7 with IC50 values between 89 and 445 μM showed stronger α‐glucosidase inhibitory activities than the antihyperglycemic drug acarbose (IC50 =1463.0±29.5 μM). However, the compounds showed lower inhibitory effects against α‐amylase and lipase with IC50 values above 500 μM than acarbose (IC50 =16.7±3.5 μM) and ursolic acid (IC50 =89.5±5.6 μM), respectively. Lineweaver‐Burk plots showed that compounds 1, 2, and 7 were non‐competitive inhibitors, compounds 4 and 5 were competitive inhibitors and compound 6 was a mixed‐type inhibitor. Fluorescence spectroscopic data showed that the compounds altered the microenvironment and conformation of α‐glucosidase. Computer simulations indicated that the compounds and enzyme interacted primarily through hydrogen bonding. The findings indicated that the compounds were inhibitors of α‐glucosidase and provided significant structural basis for understanding the binding activity of the compounds with α‐glucosidase. Abstract :